Biblical archaeology and the emergence of the kingdom of Edom - Na’Aman, Nadav (Antiguo Oriente, 2021)
Biblical Archaeology and the Emergence of the Kingdom of Edom Early Edom owes its success to the shortage of copper in the Near Eastern markets and the ability of its population to develop the copper mines in the Arabah. The revenues from the copper trade enabled the Edomites improve their life by relocating to the Negev Highlands and the eastern Beer-sheba Valley and constructing permanent settlements there. They established a polity whose centre was at Tel Masos and economic engine was at Khirbet en-Nahas in the Arabah. Shoshenq’s campaign marked a turn in the polity’s history, both politically and technologically. The Pharaoh probably set his protégé, Hadad, in the occupied territories, and through his agent controlled the Edomite polity. The Book of Kings relates the ups and downs in the relations of Judah and Edom in the 9th-early 8th centuries BCE. As long as Edom’s centres were located in the regions west of the Arabah, Judah was able to conduct campaigns and occupy its territory. The turn in relations took place in the 8th century when the Edomites established their centres on the plateau, east of the Arabah, which guaranteed them security and enabled them to develop their kingdom beyond the reach of their western neighbor.